Integrasi Profil Pelajar Pancasila dalam Pembelajaran Sejarah: Analisis Praktik dan Tantangan Guru pada Kurikulum Merdeka - Sriani, Ni Nyoman Sinta; Nuraedah, Nuraedah; Kapile, Charles; Iskandar, Iskandar (Lembaga Bale Literasi, 2026)
This study aims to analyze the integration of the Pancasila Student Profile in history learning within the Merdeka Curriculum and to identify the challenges faced by teachers in its implementation. This research employed a qualitative descriptive approach conducted at SMA Negeri 7 Palu. The subjects consisted of the principal, vice principal for curriculum, history teacher, and students. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The results show that the integration of the Pancasila Student Profile has been implemented in various stages of history learning, including preliminary, core, and closing activities. However, the implementation is still partial and not yet systematically structured. Affective dimensions such as faith and global diversity are relatively well integrated, while cognitive dimensions such as critical thinking and creativity remain less developed. Furthermore, several challenges were identified, including limited innovative teaching strategies, uneven student participation, low critical thinking skills, and time constraints in learning. This study contributes to the understanding of how the Pancasila Student Profile is integrated in history learning and highlights the need for more systematic and student-centered instructional strategies to optimize character development and higher-order thinking skills.